Psychometric analysis of the GAD-7 questionnaire in Slovak helping professionals - Katarina Krizova; Júlia Halamová; Bronislava Strnádelová; Martina Baránková (Journal of Affective Disorders Reports, 2024)
The GAD-7 is a widely used screening tool for the measurement and diagnosis of symptoms of generalized anxiety disorder. It has been translated and validated across more than 20 cultural contexts. However, no study to date examined its psychometric properties in a Slovak sample, despite the fact that a Slovak translation exists. The purpose of the present study was to test psychometric properties and factor structure of GAD-7 in a general sample of Slovak helping professionals. It was hypothesized that a one-dimensional factor structure would be supported by the data, and that construct validity would be demonstrated. A total of 2239 participants (Mage = 42.20, SD = 14.30) from different helping professions (e.g., psychologists, teachers, special educators, medical doctors, nurses, speech-language pathologists) completed an online survey. A confirmatory factor analysis yielded satisfactory factor loadings and acceptable model fit of the tested one-dimensional model. This evidence was invariant by sex. Internal consistency coefficients indicated good reliability. Significant correlations were found between the GAD-7 and both negative and positive adjustment constructs, thus demonstrating convergent and discriminant validity, respectively. The results of this study add to the evidence on the GAD-7 and its applicability across cultures and support the use of a Slovak translation of the instrument.